Sounds of War and Peace Soundscapes of European Cities in 1945 - Tańczuk, Renata; Wieczorek, Sławomir (Eastern European Studies in Musicology, 2018)
This book vividly evokes for the reader the sound world of a number of European cities in the last year of the Second World War. It allows the reader to «hear» elements of the soundscapes of Amsterdam, Dortmund, Lwów/Lviv, Warsaw and Breslau/Wrocław that are bound up with the traumatising experiences of violence, threats and death. Exploiting to the full methodologies and research tools developed in the fields of sound and soundscape studies, the authors analyse their reflections on autobiographical texts and art. The studies demonstrate the role urban sounds played in the inhabitants' forging a sense of identity as they adapted to new living conditions. The chapters also shed light on the ideological forces at work in the creation of urban sound space.